Children’s Poetry and Intersemiotic Dialogue: Poetry Theories Facing a Child Receptor who Reads Images - di Marco, Marina (Meridional. Revista Chilena de Estudios Latinoamericanos, 2017)
Regarding children’s literature, drawings have recently achieved to transpose a limit which –based on reading manners that supported the main importance of verbal aspects– assigned to them less semantic weight: with the arrival of picture books –together with avant-garde genres, such as visual poetry–, the discourse of image equaled the discourse of words. Therefore, from the perspective of the production of significance and of the reader’s participation, we consider useful the relationship between picture books and children’s poetry. Adding to the music inherent to poetry the reading pace that images involve, poetry picture books include as a common area the configuration of a world with its own meaning, the breaking of literary linearity and the problematization between the relationship subject/object. In poetry picture books, the interaction between words and images is questioned, reformulated and enriched. The present paper aims to analyze which type of ideal reader these words represent. As paradigmatic examples of the way through which this intersemiosis reformulates traditional structures, we will use two books edited in Argentina: Canción decidida, by David Wapner and Cristian Turdera (2003), and Arrorró, by Ruth Kaufman and Cristian Turdera (2013).